Anything Goes Charleston Conference Proceedings 2010 (Purdue University Press, 2011)
The Charleston Conference Proceedings documents one of the most highly regarded and influential conferences in the international library world. This volume marks and celebrates the 30th Annual Charleston Conference. The 2010 Conference focused on topics and trends in: • Collection Development • Journals and Serials Management • Technology and Product Development • Collaboration between and among Libraries and their Communities • Managing eBook and Monograph Collections